Understanding the molecular basis of flavivirus replication process for antiviral therapeutics development - Quek, Jun Ping (Nanyang Technological University, 2022)
Flavivirus is a genus of viruses belonging to the family, Flaviviridae. A few members of the genus of clinical relevance are Dengue Virus, West Nile Virus, Yellow Fever Virus, and Zika Virus. During the last decade, there were increased frequency and larger magnitude of flaviviruses’ outbreaks. However, to date, there are no antiviral treatments for these infections. In this study, different 3D x-ray crystallography structures of Zika NS2B-NS3 protease bound to different inhibitors were reported. The inhibitory effects of the compounds on NS2B-NS3 protease were also characterized. Next, structural studies using both x-ray crystallography and electron microscopy were also used to examine viral RNA recognition by NS5 polymerase. Reconstitution studies were also performed to assemble and characterize the minimal replication complex. By understanding their molecular interactions with substrates and inhibitors, it will aid in the development of antiviral drugs that target different stages of the flavivirus’ lifecycle.